Snacking hysteria: Communication motive behind excessive aci snack consumption - Mutia, Lu'lu; Dida, Susanne; Lusiana, Elnovani (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This qualitative study explores the motives of alpha generation from elementary school students in Jatinangor District who consume excessive amounts of aci snacks. The paradigm used is interpretive with a qualitative approach. The research subject is the experiences of alpha generation, and the data collection techniques involve observation and in-depth interviews. The result shows that alpha generations have a high hysteria towards aci snacks, because of the affordable price, established habits, and social environmental influences. The consumption of aci is not only influenced by physiological needs (delay hunger) but also social and economic factors. Therefore, this phenomenon emphasizes the urgent need to build health literacy in the school environment and supported by family environment.